Cardiovascular magnetic resonance feature tracking derived strain analysis can predict return to training following exertional heatstroke - Jun Zhang; Song Luo; Li Qi; Shutian Xu; Dongna Yi; Yue Jiang; Xiang Kong; Tongyuan Liu; Weiqiang Dou; Jun Cai; Long Jiang Zhang (Journal of Cardiovascular Magnetic Resonance, 2024)
ABSTRACT: Background: Exertional heatstroke (EHS) is increasingly common in young trained soldiers. However, prognostic markers in EHS patients remain unclear. The objective of this study was to evaluate cardiovascular magnetic resonance (CMR) feature tracking derived left ventricle (LV) strain as a biomarker for return to training (RTT) in trained soldiers with EHS. Methods: Trained soldiers (participants) with EHS underwent CMR cine sequences between June 2020 and August 2023. Two-dimensional (2D) LV strain parameters were derived. At 3 months after index CMR, the participants with persistent cardiac symptoms including chest pain, dyspnea, palpitations, syncope, and recurrent heat-related illness were defined as non-RTT. Multivariable logistic regression analysis was used to develop a predictive RTT model. The performance of different models was compared using the area under curve (AUC). Results: A total of 80 participants (median age, 21 years; interquartile range (IQR), 20–23 years) and 27 health controls (median age, 21 years; IQR, 20–22 years) were prospectively included. Of the 77 participants, 32 had persistent cardiac symptoms and were not able to RTT at 3 months follow-up after experiencing EHS. The 2D global longitudinal strain (GLS) was significantly impaired in EHS participants compared to the healthy control group (−15.8 ± 1.7% vs −16.9 ± 1.2%, P = 0.001), which also showed significant statistical differences between participants with RTT and non-RTT (−15.0 ± 3.5% vs −16.5 ± 1.4%, P < 0.001). 2D-GLS (≤ −15.0%) (odds ratio, 1.53; 95% confidence interval: 1.08, 2.17; P = 0.016) was an independent predictor for RTT even after adjusting known risk factors. 2D-GLS provided incremental prognostic value over the clinical model and conventional CMR parameters model (AUCs: 0.72 vs 0.88, P = 0.013; 0.79 vs 0.88, P = 0.023; respectively). Conclusion: Two-dimensional global longitudinal strain (≤ −15.0%) is an incremental prognostic CMR biomarker to predict RTT in soldiers suffering from EHS.